Selective Capsulotomies and Partial Capsulectomy in Implant-Based Breast Reconstruction Revision Surgery - Pietro Susini; Gianluca Marcaccini; Francesco Ruben Giardino; Mirco Pozzi; Francesco Volanti; Giuseppe Nisi; Roberto Cuomo; Luca Grimaldi (The Breast Journal)
Background. Breast cancer with about 2.3 million diagnoses and 685,000 deaths globally is the most frequent malignancy in the female population. Continuous research has led to oncological and reconstructive advances in the management of breast cancer, thus improving outcomes and decreasing patient morbidity. Nowadays, the submuscular expander and prosthesis (E/P) implant-based breast reconstruction (IBR) accounts for 73% of all reconstructions. Despite its widely accepted efficacy, the technique is not free from complications and up to 28% of cases require revision surgery for mechanical complications such as capsular contracture, implant displacement/rotation, and implant rupture. With this study, the authors report their experience in the management of E/P IBR revision surgery through the technique of Selective Capsulotomies (SCs) and Partial Capsulectomy (PC). Methods. A retrospective study was conducted on patients who had previously undergone E/P IBR and presented for revision reconstruction between January 2013 and May 2023 at the Department of Plastic Surgery of the University of Siena, Italy. Reasons for revision included capsular contracture, implant displacement/rotation, and implant rupture. Revision reconstructions involved SC and PC with implant replacement. Fat grafting was also considered. The complication rate was evaluated by analysis of patients’ medical records. Patients’ satisfaction with the treatment was assessed through a specific questionnaire. Results. 32 patients underwent revision surgeries. No early complication occurred. Recurrence rate was assessed at 19% with average follow-up of 59 months (range: 13–114 months). The average time between revision surgery and recurrence was 3 years (range: 1–6 years). 23 patients answered the questionnaire and were overall satisfied with the treatments (8.29/10). Conclusions. SC possibly associated to PC is a valuable option for E/P IBR revision surgery with minimal complications, reduced surgical trauma, short operating time, and relatively low recurrence risk. In addition, treated patients are overall satisfied with the results over time.